Technical considerations on the peritonitic forms of postoperative necrotizing enteritis: about 2 observations - Perdomo, Roberto (Cirugía del Uruguay, 2020)
Two cases of post-operative necrotizing enteritis, of the peritonitic type, treated surgically and with a favorable course, are reported upon. A number of features underlying the surgical technique used in these cases, are considered. The following conclusions are reached: 1) The greater extension of the mucous tissue lesions requires a careful examination in order to determine the safety level for consecutive resection and anastomosis. 2) Simple closure with re-inforcement intestinal folding according to the technique advocated by Noble for perforated cases, has proved of great usefulness and ready application.